El autoaprendizaje como herramienta de trabajo a través de la lectura en ELE Estrategias de aprendizaje autónomo y proyecto de diario - Clara García Reguera 1998- (2023)
In this study completed to fulfil the requirements for the MA Spanish degree from the Faculty of Languages and Cultures by the University of Iceland, the main emphasis is on thedevelopment of a diary based on reading in Spanish as a Second Language, used as the medium to compile the process of self-learning and interiorize this way of studying through using learning strategies. The development of this approach will be structured in a theoretical revision concerning the self-learning model along with reading as a mechanism in a second language, followed by its practical application. The first section approaches the concept of autonomy when it comes to the learning area, emphasizing the various distinctions narrowing it to define the chosen model, which leads to the theoretical introduction and classification of the learning strategies according to Rebeca Oxford. Said method will be contextualized at the university structure that is taken in account. Thus, the personal traits that will compel the students throughout this process will also be supported, those being the emotions and its treatment to strengthen and associate them while learning. In addition, it will also be observed from the professor’s point of view, who will have a major role during the process as a support model. Once those precepts have been settled, the theoretical phase will continue during the second section where reading will be the central topic; a formal approach considering the main references about this skill following the CEFR (2002) and the Plan Curricular (2008), to finish with its inclusion and fusing it according to the self-learning. After said contextualization, the third section initiates the practical phase exposing the characteristics of both the organization of the subject “Conversation I” and the aimed group of students. Consequently, the formal criteria will be mentioned and adapted to self-learning, such as the learning project and the evaluation. The main goals will be proposed, highlighting the autonomy of the students ...